Expert Evaluation of Methodical Work in an Educational Institution - Панченко, Алла Гнатівна (Educological discourse, 2014)
The article deals with necessity of using expert estimation of methodical work as an instrument to stimulate the secondary school development. The author proposed some items to estimate the level of methodical work organization in an educational institution.